The Use of Role-Play to Improve Speaking Ability at MTs Samarinda - sumaningsih - (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Abstract: The preliminary study in teaching speaking at MTs AlMuna Samarinda was not satisfied; the students were reluctant to speak English, were shy and not confident to express ideas orally, and were afraid of being ridiculed by their friends. Their speaking skills' average score was 63.06, and it was below the minimum passing grade, that is, 70. This study tried to improve the students' ability to speak through role-play. The action research was carried out in two stages. The instruments of the study are observation, documentation, and speaking test. The findings of the study show that role-play could improve the students' speaking ability. It was proven by improving their speaking skill, from 63.06 in the preliminary study up to 76.6 in cycle II. Abstrak: Hasil studi pendahuluan dalam pembelajaran speaking di MTs AlMuna Samarinda tidak memuaskan; siswa enggan berbicara bahasa Inggris, mereka malu-malu dan tidak percaya diri untuk mengungkapkan ide secara lisan, dan mereka takut ditertawakan oleh teman-temannya. Nilai rata-rata keterampilan berbicara siswa adalah 63,06 dan berada di bawah nilai kelulusan minimal yaitu 70. Penelitian ini berusaha untuk meningkatkan kemampuan berbicara siswa melalui permainan peran. Penelitian tindakan ini dilakukan dalam dua siklus. Instrumen penelitian adalah observasi, dokumentasi, dan tes berbicara. Temuan penelitian menunjukkan bahwa permainan peran dapat meningkatkan kemampuan berbicara siswa. Hal itu dibuktikan dengan peningkatan kemampuan berbicara mereka dari 63,06 pada pembelajaran pendahuluan menjadi 76,6 pada siklus II. Kata-kata kunci: speaking, ELT, bermain peran